Teaching plant-animal interactions with active student participation and deep learning - Altenburger, Andreas (Improving University Science Teaching and Learning, 2023)
Teachers can improve their performance and thus students’ learning outcome through systematic reflection on their teaching (Sølberg, 2015). And teaching and learning can be improved by adding variation in teaching methods and learning activities (Weimer, 1990). This paper reports the results of a didactical research project and is a reflection on planning and teaching a three-hour session for master students in the course ‘Plant Animal Interactions. An Evolutionary Approach’ in the fall semester 2016 at the University of Copenhagen. I used recommendations described by Peter Stray Jørgensen (Jørgensen, 2015) and Donald A. Bligh (Bligh, 2000) to plan the session. The aim of the research project was to identify teaching methods that improve the student learning outcome of my teaching. I did this by adding five diverse learning activities throughout the session (lectures, microscopy, student experiment, experiment analysis, and presentation of experiment results). The students evaluated the perceived effectiveness of each learning activity immediately after the session in a questionnaire.